2001
DOI: 10.1097/00005373-200108000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in Damage Control for Exsanguinating Penetrating Abdominal Injury

Abstract: Continued application of DC principles has led to improved survival with PAI. Better control of temperature, experience with the open abdomen, and intensive care unit care may be causative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
181
1
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 315 publications
(195 citation statements)
references
References 75 publications
3
181
1
10
Order By: Relevance
“…[97][98][99] To classify patients in a critical condition, general surgeons use the term ''triad of death,'' 81 consisting of the degree of shock, hypothermia, and coagulopathy. 109 Although these factors have been largely tested in patients with penetrating injuries, 110 we confirmed that they are also relevant for patients with blunt trauma and appear to be feasible for use in the decision-making process in the emergency room. 42,111 Additionally, we determined that the polytrauma patient with blunt injuries has additional problems in terms of soft tissue injuries which are underrepresented if the ''triad of death'' is used alone classify the patient.…”
Section: Resultssupporting
confidence: 60%
“…[97][98][99] To classify patients in a critical condition, general surgeons use the term ''triad of death,'' 81 consisting of the degree of shock, hypothermia, and coagulopathy. 109 Although these factors have been largely tested in patients with penetrating injuries, 110 we confirmed that they are also relevant for patients with blunt trauma and appear to be feasible for use in the decision-making process in the emergency room. 42,111 Additionally, we determined that the polytrauma patient with blunt injuries has additional problems in terms of soft tissue injuries which are underrepresented if the ''triad of death'' is used alone classify the patient.…”
Section: Resultssupporting
confidence: 60%
“…Despite the use of damage control in trauma patients, the mortality-associated damage control has been reported above 40% in some series [114][115][116][117][118][119][120].…”
Section: Viability Of the Bowelmentioning
confidence: 99%
“…In the literature, the timing of angiography in the management of severe liver trauma is controversial. According to Johnson et al, severe hepatic injury, of AAST grade IV or more, is an indication for immediate postoperative angiography (21). Our data showed that angiography after initial damage control surgery may not always be needed.…”
Section: Grade 3 4 17mentioning
confidence: 53%